2022
DOI: 10.1108/acmm-06-2022-2664
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion behavior research and corrosion prediction of structural steel in marine engineering

Abstract: Purpose This paper aims to reveal the corrosion mechanism and corrosion development regulation of marine engineering structural steel in the marine environment and provide constructive suggestions for marine immersed tunnel engineering. Design/methodology/approach In this study, marine engineering structural steel’s behavior and corrosion prediction were carried out under the conditions of no cathodic protection and under-protection by artificially adding dissolved oxygen in a simulated seawater solution as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The corrosion of CoCrNi MEA in different states in NaCl solutions at 25°C was determined using cyclic potentiodynamic polarization (Cao et al , 2022). Figure 5 shows the cyclic polarization curves of CoCrNi MEA in different states in 3.5 Wt.% NaCl solution.…”
Section: Resultsmentioning
confidence: 99%
“…The corrosion of CoCrNi MEA in different states in NaCl solutions at 25°C was determined using cyclic potentiodynamic polarization (Cao et al , 2022). Figure 5 shows the cyclic polarization curves of CoCrNi MEA in different states in 3.5 Wt.% NaCl solution.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the stress concentration of triangular pits was more obvious than that of circular pits, and the fatigue strength reduced more seriously. Therefore, the severity of pit corrosion was much higher than other corrosion types for steel wire (Cao et al 2022; Guo et al , 2021). In addition, the above studies focused on the relationship between the corrosion degree and mechanical properties, rarely involving the degradation law of fracture behavior of corroded steel wire.…”
Section: Introductionmentioning
confidence: 90%
“…A destructive corrosion caused by the electrochemical reaction of metallic structures in marine environment is called seawater corrosion 1–5 . Seawater is the most abundant and corrosive natural electrolyte solution in nature 6 . China has a vast sea area, with a coastline of 18,000 km on the mainland and 14,000 km on more than 6500 islands, covering a sea area of nearly 3 million km 2 7,8 .…”
Section: Introductionmentioning
confidence: 99%